Mill dams impact microbiome structure and depth distribution in riparian sediments - Kan, Jinjun; Peck, Erin K.; Zgleszewski, Laura; Peipoch, Marc; Inamdar, Shreeram (Frontiers in Microbiology, 2023)
Damming has substantially fragmented and altered riverine ecosystems worldwide. Dams slow down streamflows, raise stream and groundwater levels, create anoxic or hypoxic hyporheic and riparian environments and result in deposition of fine sediments above dams. These sediments represent a good opportunity to study human legacies altering soil environments, for which we lack knowledge on microbial structure, depth distribution and ecological function. Here we compared bacterial/archaeal and fungal community structure (diversity and composition) and functional genes (i.e., nitrification and denitrification) at different depths (ranging from 0 - 4 m) in riparian sediments above breached and existing milldams in the Mid-Atlantic United States. We found significant location- and depth-dependent changes in microbial community structure. Proteobacteria, Bacteroidetes, Firmicutes, Actinobacteria, Chloroflexi, Acidobacteria, Planctomycetes, Thaumarchaeota, and Verrucomicrobia were the major prokaryotic components while Ascomycota, Basidiomycota, Chytridiomycota, Mortierellomycota, Mucoromycota, and Rozellomycota dominated fungal sequences retrieved from sediment samples. Ammonia oxidizing genes (amoA for AOA) were higher at the sediment surface but decreased sharply with depth. Besides top layers, denitrifying genes (nosZ) were also present at depth, indicating a higher denitrification potential in the deeper layers. However, these results contrasted with in-situ DEA (denitrification enzyme assay) measurements, suggesting the presence of dormant microbes and/or other nitrogen processes in deep sediments that compete with denitrification. In addition to enhanced depth stratification, our results also highlighted that dam removal increased species richness, microbial diversity and nitrification. Lateral and vertical spatial distributions of soil microbiomes (both prokaryotes and fungi) suggest that not only sediment stratification but also concurrent watershed conditions are important in explaining the depth profiles of microbial communities and functional genes in dammed rivers.